New host, geographic records, and histopathologic studies of Angiostrongylus spp (Nematoda: Angiostrongylidae) in rodents from Argentina with updated summary of records from rodent hosts and host specificity assessment - Robles, María del Rosario (2016)
To date, 21 species of the genus Angiostrongylus (Nematoda: Angiostrongylidae) have been reported around the world, 15 of which are parasites of rodents. In this study, new host, geographic records, and histopathologic studies of Angiostrongylus spp in sigmodontine rodents from Argentina, with an updated summary of records from rodent hosts and host specificity assessment, are provided. Records of Angiostrongylus costaricensis from Akodon montensis and Angiostrongylus morerai from six new hosts and geographical localities in Argentina are reported. The gross and histopathologic changes in the lungs of the host species due to angiostrongylosis are described. Published records of the genus Angiostrongylus from rodents and patterns of host specificity are presented. Individual Angiostrongylus species parasitise between one-19 different host species. The most frequent values of the specificity index (STD) were between 1-5.97. The elevated number of host species (n = 7) of A. morerai with a STD = 1.86 is a reflection of multiple systematic studies of parasites from sigmodontine rodents in the area of Cuenca del Plata, Argentina, showing that an increase in sampling effort can result in new findings. The combination of low host specificity and a wide geographic distribution of Angiostrongylus spp indicates a troubling epidemiological scenario although, as yet, no human cases have been reported.